GREEN ENERGY TRANSITION IN AZERBAIJAN: ANALYZING SURVEY RESULTS - Guliyev, Magsud (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The global community has set a target to reduce greenhouse gases and ensure the continuation of the planet's livability. The world countries have committed to doing their part with respect to climate change, inclusivity, affordability, and many other global challenges. In light of the global transition, as a valuable partner of the global community, Azerbaijan adopted national priorities to reach green growth and green energy production by 2030. This research aims to cast a light on the green transition and, through the survey method, to reveal Azerbaijani people's approaches toward renewable energy. The survey questions encompass people's opinions on fossil fuels, climate change responsibility, the reasons causing it, electric vehicles, people's inclination toward purchasing electric automobiles, and the most problematic issues in the transition to green energy.